Comparison of Blood Gas Analysis on Hemodialysis in Patients with Chronic Kidney Diseases - Nenden Senina Rindaha; Sulina Yanti Wibawa; Yuyun Widaningsih; Rachmawati A. Muhiddin (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Chronic Kidney Disease (CKD) is defined as a renal failure that has lasted for more than three months. Hemodialysis is thetype of kidney replacement therapy that is mostly used, and blood gas analysis can be used to identify this condition. Thisstudy is to compare the blood gas analysis on pre-and post-dialysis in patients with CKD using pH, PaCO , PaO , HCO , SO , 2 2 3 2and BE as markers of improvement in the patients'condition. The population was all patients diagnosed with CKD andhemodialysis at Wahidin Sudirohusodo Hospital, and eligible according to the criteria in this study. The sample size wasdetermined using Federer's calculation, and the statistical analysis using paired T-test and Wilcoxon signed-rank test withα=0.05. Subjects were 34 patients, consisting of 18 females (52.9%) and 16 males (47.1%). Hemodialysis had the mostsignificant impact on the PaO and SaO variables. Relation between PaO and SaO was illustrated in a sigmoid curve. 2 2 2 2Oxygen-bound hemoglobin increased after the first molecule was bound. An almost full PaO pressure will cause a slight 2increase in SaO . Whereas at <90% saturation, a slight decrease in PaO will cause a large decrease in SaO . PaO and SaO 2 2 2 2 2determine cardiac efficiency and the markers for assessing the metabolic conditions of the lungs and heart that correlatewith oxygen. Chronic kidney disease patients experienced improved conditions after undergoing hemodialysis withincreased blood gas values, especially in PaO and SaO .